A Hyperelliptic Curve Cryptosystem Based Proxy Promised Signcryption Scheme. (27th April 2022) - Khan, Farhad Ullah; Algarni, Fahad; Ullah, Insaf; Karamti, Hanen; Manzar, Muhammad Anwaar; Alzahrani, Ahmed Saeed; Aziz, Muhammad Adnan; Khan, Muhammad Asghar
Abstract : Signcryption is the method of combining a digital signature with encryption in a single logical step to get the cryptographic primitives of a public key. However, in addition to signcryption, we sometimes require anonymity and delegation of rights. In this paper, we propose a scheme called proxy promised signcryption to address all of these objectives simultaneously. In this scheme, the actual sender or signer delegates authority to an agent known as signcrypter for signcryption of the actual ciphertext. The agent entity is facilitated to generate a promised signcrypted text. The signcrypted text is then communicated to the intended recipient. The proposed work aims to reduce computation and communication costs, which has been tested by comparing it to existing schemes. The results obtained from this comparison support the aims of our scheme. The proposed scheme's security has also been evaluated using the Automated Validation of Internet Security Protocols and Applications (AVISPA) tool. The results validate that our scheme resists well-known cyberattacks.